Genotype-functional-phenotype correlations in photoreceptor guanylate cyclase (GC-E) encoded by GUCY2D. (March 2018) - Sharon, Dror; Wimberg, Hanna; Kinarty, Yael; Koch, Karl-Wilhelm
Abstract: The GUCY2D gene encodes for the photoreceptor guanylate cyclase GC-E that synthesizes the intracellular messenger of photoreceptor excitation cGMP and is regulated by intracellular Ca 2+ -sensor proteins named guanylate cyclase-activating proteins (GCAPs). Over 140 disease-causing mutations have been described so far in GUCY2D, 88% of which cause autosomal recessive Leber congenital amaurosis (LCA) while heterozygous missense mutations cause autosomal dominant cone-rod degeneration (adCRD). Mutations in GUCY2D are one of the major causes of all LCA cases and are the major cause of adCRD. A single amino acid, arginine at position 838, is likely to be the most sensitive one in GC-E as four single mutations and two complex mutations were reported to affect R838. The biochemical effect of 45 GC-E variants was studied showing a clear genotype-phenotype correlation: LCA-causing mutations either show reduced ability or complete inability to synthesize cGMP from GTP, while CRD-causing mutations are functional, but shift the Ca 2+ -sensitivity of the GC-E − GCAP complex. Eight animal models of retinal guanylate cyclase deficiency have been reported including knockout (KO) mouse and chicken models. These two models were used for gene augmentation therapy that yielded promising results. Here we integrate the available information on the genetics, biochemistry and phenotype that is related to GUCY2D mutations. These data clearly show that mutation type (missense versus null) and localization (dimerization domain versus other protein domains) are correlated with the pattern of inheritance, impact on enzymatic function and retinal phenotype. Such clear correlation is unique to GUCY2D while mutations in many other retinal disease genes show variable phenotypes and lack of available biochemical assays. Highlights: GUCY2D mutations cause different retinal phenotypes with different inheritance patterns. Biochemical analysis of GC-E variants shows a clear genotype-phenotype correlation. Cone-rod degeneration mutations are clustered in the dimerization domain. Amino acid 838 is the most sensitive GC-E position affected by six different mutations.